Transformasi Mutu Pendidikan Islam Berbasis Total Quality Management di Madrasah Aliyah Nurul Jadid - Ahmad Faidul Mannan; Misbahul Arifin; Tiara Nurul Annisa' (Educational Research Center, 2025)
This study aims to examine the integration between the basic concepts of quality management in Islamic education with the principles of Total Quality Management (TQM) in the context of Islamic boarding school-based madrasahs. Islamic educational institutions currently face major challenges in ensuring the quality of education that is in line with the demands of the times and Islamic values. A qualitative-descriptive approach with a multiple case study design was used in this study, with three madrasahs in East Java and Central Java as the objects. Data collection techniques include in-depth interviews, participatory observation, and quality documentation studies. The results of the study indicate that the integration of Islamic values ​​(such as amanah, ihsan, deliberation, and sincerity) with the principles of TQM (continuous improvement, stakeholder focus, and teamwork) is able to form an effective quality management system with an Islamic character. This model results in increased student and parent satisfaction, and strengthens a value-based quality culture. This study suggests the development of a conceptual model of Islamic Education Quality Management-TQM as a strategic guideline for contemporary Islamic educational institutions.